Clinical Response and Transfusion Reactions of Sheep Subjected to Single Homologous Blood Transfusion - Rejane Santos Sousa; Antonio Humberto Hamad Minervino; Carolina Akiko Sato Cabral Araújo; Frederico Augusto Mazzocca Lopes Rodrigues; Francisco Leonardo Costa Oliveira; Clara Satsuki Mori; Janaina Larissa Rodrigues Zaminhan; Thiago Rocha Moreira; Isadora Karolina Freitas Sousa; Enrico Lippi Ortolani; Raimundo Alves Barrêto Júnior (The Scientific World Journal)
Studies in relation to blood conservation and responses to transfusion are scarce for ruminants. We evaluated the clinical manifestations of sheep that received a single homologous transfusion of whole blood, focusing on transfusion reactions. Eighteen adult sheep were subjected to a single phlebotomy to withdraw 40% of the total blood volume, which was placed into CPDA-1 bags and then divided into G0, animals that received fresh blood, and G15 and G35, animals that received blood stored for 15 or 35 days, respectively. Clinical observations were recorded throughout the transfusion, whereas heart rate, respiratory rate, and rectal temperature were assessed at the following times: 24 hours after phlebotomy and before transfusion; 30 minutes, six, twelve, 24, 48, 72, and 96 hours and eight and 16 days after transfusion. All groups presented transfusion reactions, among which hyperthermia was the most frequent (50% of animals). Tachycardia occurred most frequently in the G35 animals (50% of them). During transfusion G35 animals presented more clinical manifestation (P<0.05). Transfusion of fresh or stored total blood improved the blood volume, but transfusion reactions occurred, demonstrating that a single transfusion of fresh or stored blood can cause inflammatory and febrile nonhemolytic transfusion reactions in sheep.